England's citizenship education experiment : state, school and student perspectives - Jerome, Lee (Bloomsbury, 2012)
How do we prepare young people to understand the complex problems confronting our society and their place as citizens in shaping solutions? Until 1997, the contribution of schools to these challenges was ad hoc and uncoordinated, but with the introduction of citizenship education into the National Curriculum in England a new political project began. Between 2002 and 2012, England has become a leading player in the debate about how to induct young people into democracy. Jerome explores the connections between the values promoted by the government and the forms of citizenship promoted through.